Penentuan Penampungan Korban Banjir Di Kecamatan Laweyan Kota Surakarta Berbasis Sistem Informasi Geografis - Moh. Ali Ma'sum (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2021)
One of the anticipation actions that can be done before the flood disaster comes is to determine the evacuation route and evacuation location or shelter for flood relief and spread to the public in order to accelerate the process of evacuation of disaster victims so as to minimize losses from the flood itself. This research was conducted by approaching Geographic Information System (SIG) The purpose of this research is (1) Knowing the flood-prone agihan in Laweyan Subdistrict based on SIG. (2) Analyze the Availability of Shelter Locations (Educational Buildings and Buildings of Worship) of flood victims in Laweyan Subdistrict. It is expected that in the research to know the potential of the best temporary evacuation shelter / protection and evacuation design so that it can be considered and help the relevant agencies, especially local BPBD in order to improve flood mitigation in Sumber Village, Banjarsari District, Surakarta City. To reduce or overcome the impact caused by flood disasters on the comfort and safety of the community in Laweyan Subdistrict, researchers need to raise the title,